1975
DOI: 10.1111/j.1469-7998.1975.tb03189.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of running by quail (Coturnix)

Abstract: A force platform has been used to obtain records of the forces exerted on the ground by running quail. These records, with cinematograph film taken simultaneously, have been used to determine the fluctuations of kinetic and potential energy occurring during a step. This gives a first estimate of the energy required for running. Graphs of force against length changes during a step have been calculated for the major leg muscles, making certain assumptions. These graphs provide a second estimate of the energy req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1
1

Year Published

1981
1981
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 10 publications
3
54
1
1
Order By: Relevance
“…For both birds, this acceleration peak occurred while the bird was still on the perch. The observed maximal vertical force production (F z ) was greater than that reported in other studies: 1.3-2.3 ϫ body weight in pigeon compared with 2.9-3.6 ϫ body weight in diamond dove and 3.6-8.3 ϫ body weight in zebra finch (Clark and Alexander, 1975;Heppner and Anderson, 1985;Bonser and Rayner, 1996). We also observed that relative hindlimb forces produced by the dove (m50g) were 55±2.5% lower than in the finch (m15g), which was consistent with the hypothesis that the maximal acceleration generated across species should be inversely proportional to body weight (Bonser and Rayner, 1996).…”
Section: Discussioncontrasting
confidence: 45%
“…For both birds, this acceleration peak occurred while the bird was still on the perch. The observed maximal vertical force production (F z ) was greater than that reported in other studies: 1.3-2.3 ϫ body weight in pigeon compared with 2.9-3.6 ϫ body weight in diamond dove and 3.6-8.3 ϫ body weight in zebra finch (Clark and Alexander, 1975;Heppner and Anderson, 1985;Bonser and Rayner, 1996). We also observed that relative hindlimb forces produced by the dove (m50g) were 55±2.5% lower than in the finch (m15g), which was consistent with the hypothesis that the maximal acceleration generated across species should be inversely proportional to body weight (Bonser and Rayner, 1996).…”
Section: Discussioncontrasting
confidence: 45%
“…During stance, the orientation of the ground reaction force shifts from knee extension early in stance to knee flexion in midthrough late stance (Clark and Alexander, 1975;Roberts et al, 1998) (R.L.M. and J. Rubenson, unpublished observations).…”
Section: Coactivation Of the Fclp And Fclamentioning
confidence: 99%
“…Likewise, analyses of joint rotation are usually restricted to flexion/extension (FE) angles (Sigmund, 1959;Cracraft, 1971;Rylander and Bolen, 1974;Jacobson and Hollyday, 1982;Manion, 1984;Gatesy, 1990;Gatesy, 1999;Johnston and Bekoff, 1992;Abourachid and Renous, 2000;Reilly, 2000;Verstappen et al, 2000;Ellerby and Marsh, 2010;Smith et al, 2010;Nyakatura et al, 2012). Given the relatively small transverse component of the ground reaction force during forward locomotion (Clark and Alexander, 1975;Main and Biewener, 2007;Troy et al, 2009), inverse dynamic studies normally emphasize net FE joint moments as well (Roberts, 2001;Roberts and Scales, 2004;Daley et al, 2007;Rubenson and Marsh, 2009;Andrada et al, 2013b). Our current perception of bird hind limbs thus remains deeply rooted in the erect paradigm.…”
Section: Introductionmentioning
confidence: 99%